Foreign Direct Investments: Asian and European Transition Economies - Teker, Suat; Tuzla, Hayri; Pala, Aynur (International Journal of Economics and Financial Issues, 2013)
Transition economies in Asian and European region have been showing a great performance and attracting large sum of foreign direct investments in recent years. Although the foreign direct investments totaled only 500 million USD in 1992 for all these transition countries, it is around 270 billion USD as of 2011. This study investigates the trends and dispersion of foreign direct investments in these two geographically distinct regions for the period of 1992-2011. The results show that the transition economies in the Asian side look to perform better for accumulating much larger sum of foreign direct investments while the transition economies in the European side are more successful for having a higher foreign direct investments per capita. Keywords: Transition economies; foreign direct investments; economic growth. JEL Classifications: F21; F41